Enhancing Taxpayer Compliance through E-Filing and E-Billing: Evidence from Jayapura, Indonesia - Sutisna, Entis; Fachril, Fadriansyah (Advances: Jurnal Ekonomi & Bisnis, 2023)
Purpose: This study aims to empirically examine the impact of E-Filing and E-Billing on individual taxpayer compliance at the Jayapura Primary Tax Service Office in Indonesia. The study hypothesizes that both E-Filing and E-Billing positively and significantly influence taxpayer compliance by simplifying tax reporting and payment processes, improving efficiency, and enhancing accessibility. Research Design and Methodology: This study adopts a descriptive quantitative approach and utilizes primary data collected through structured questionnaires distributed to 100 individual taxpayers registered at the Jayapura Primary Tax Service Office. The research employs multiple linear regression analysis, including descriptive statistical analysis, validity and reliability tests, normality tests, multicollinearity and heteroscedasticity tests, and hypothesis testing using the coefficient of determination and partial tests (t-test). The study controls external factors influencing taxpayer compliance, ensuring that the observed relationships between E-Filing, E-Billing, and taxpayer compliance remain valid and reliable. Findings and Discussion: The empirical results indicate that E-Filing and E-Billing significantly and positively affect taxpayer compliance. The findings suggest that E-Filing facilitates a more efficient and transparent tax reporting process, reducing administrative burdens and encouraging taxpayers to fulfill their obligations on time. Similarly, E-Billing enhances compliance by offering a more accessible and user-friendly payment system, allowing taxpayers to meet their tax obligations seamlessly. These results align with the Technology Acceptance Model (TAM) and Theory of Reasoned Action (TRA), which explain how perceived usefulness and ease of use influence individuals’ adoption of digital tax services. Implications: The findings provide valuable insights into tax authorities, policymakers, and financial regulators regarding the importance of digital tax administration systems in improving taxpayer compliance. Future research should explore additional factors influencing compliance, such as tax knowledge, penalties, and incentives, and conduct comparative studies across different regions to provide a broader understanding of the effectiveness of digital tax services.